HAWAIIS ECOLOGICAL IMPERIALISM: POSTCOLONIAL ECOCRITICISM READING ON KIANA DAVENPORTS SHARK DIALOGUES - Kristiawan Indriyanto (Sanata Dharma University, 2019)
Recent studies of postcolonialism have explored the interconnection between postcolonial and environmental/eco-criticism. Studies from Huggan (2004), Nixon (2005), Cilano and DeLoughrey (2007) counter the underlying assumption that these criticisms stand in opposition toward each other by pointing out the overlapping areas of interest between postcolonial and ecocriticism and the complementary aspect of these two criticisms (Buell, 2011). Postcolonial ecocriticism, as theorized by Huggan and Tiffin (2010) and DeLoughrey and Handley (2011) asserts the intertwined correlation between environmental degradation and the marginalization of the minority/indigenous ethic groups which inhabit a particular place. The underlying capitalist and mechanistic ideologies in which nature is perceived only of their intrinsic values and usefulness toward (Western) humans illustrates total disregard to the original owner of the colonized land, the indigenous people. This perspective is underlined by Serpil Oppermanns (2007) concept of ecological imperialism to underline the anthropocentric perspective that legitimate Western domination toward the colonies natural resources. Although discussion of postcolonial ecocriticism has encompassed diverse regions such as Caribbean, Africa and Asia, scant attention has been given toward Pacific archipelago especially Hawaii. Through reading on Kiana Davenports Shark Dialogues (1994), this paper explores how American colonialism results in ecological imperialism in this island chain. It is hoped that this analysis can contribute toward enriching the discussion on postcolonial ecocriticism.